The profile of the achievement motivation and its motivational mediators as perceived by senior clinicians A.Y. 2003-2004 - Bumotad, Earl F.; Nepomuceno, Czarina Al H.; Tumang, Heherson M. (Co-Author/Adviser).
The University of the Philippines College of Dentistry is one of the colleges that have been identified to have the highest attrition rate. This study aimed to look into the achievement motivation profile of the current senior clinicians utilizing the Thematic Apperception Test (TAT), a tool that measures the implicit or unconscious motivation of individuals. A self-report questionnaire on the various motivational mediators as perceived by the students was accomplished. A descriptive study was conducted from September 2003 to January 2004 at the University of the Philippines College of Dentistry. The target population is the 35 senior clinicians during A.Y. 2003-2004. Using convenience sampling, only 20 subjects (57.14%) were generated. This was the sample on which the TAT and the self-report questionnaire were administered. The group showed a disturbingly low achievement motivation in spite of the satisfactory GWA (mean=2.401). They also have good formal and informal relationship with their teachers. A cooperative type of teacher-student relationship was perceived to be predominant in the college. As regards to the different variables that contribute to the good teacher-student relationship, they believe that their personality, having common interest with the teachers, positive disposition and attitude contribute to the favorable interaction. However, they do not see their social economic status, gender, and teacher's gender as any factor that would affect the teacher-student interaction. In terms of the different motivational variables, they perceive that they assume learning goals in most of the disciplines. They generally see themselves as having high interest on the task, very competent in terms of cognitive and manual skills and the resources available to them do not pose as obstacles, which make them perceive that the task is moderately difficult.. However, due to the high standards, teacher expectation and evaluative tools, they exert more time and effort (indicative of their persistence) to accomplish the tasks. Unfortunately, they see that the results of all their efforts are not congruent to the efforts they exert. Nonetheless, the group gave a fair rate in their chances of completing their requirements on time but they attribute this more on intrinsic factors. In conclusion, all variables of achievement are favorable for the subjects but the group generally assumes performance goals. The group has a very low implicit achievement motivation and has a satisfactory GWA (2.401).
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Motivation in education; Students, Dental -- 2003-2004 -- University of the Philippines